1993
DOI: 10.1042/bj2910677
|View full text |Cite
|
Sign up to set email alerts
|

The bioactive phospholipid lysophosphatidic acid is released from activated platelets

Abstract: Lysophosphatidic acid (LPA) is a water-soluble phospholipid with hormone-like and growth-factor-like activities. LPA activates a putative G-protein-coupled receptor in responsive cells, but the natural source of exogenous LPA is unknown. Here we show that LPA is present in mammalian serum in an active form (bound to albumin) at concentrations of 1-5 microM, but is not detectable in platelet-poor plasma, suggesting that LPA is produced during blood clotting. We find that thrombin activation of platelets prelabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
430
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 619 publications
(444 citation statements)
references
References 33 publications
14
430
0
Order By: Relevance
“…This simple phospholipid has all the hallmarks of a new class of signalling molecule, and it will be of great interest to determine whether LPA or PA generated metabolically have similar signalling functions. However the observations that serum contains LPA [28], and that activated platelets secrete the phospholipid, suggest that a model involving interaction with a surface receptor is physiologically feasible. It is also of considerable interest that LPA activates the MAP kinase cascade (see also [12]), raising the possibility that a kinase associated with this cascade is responsible for Cx43 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…This simple phospholipid has all the hallmarks of a new class of signalling molecule, and it will be of great interest to determine whether LPA or PA generated metabolically have similar signalling functions. However the observations that serum contains LPA [28], and that activated platelets secrete the phospholipid, suggest that a model involving interaction with a surface receptor is physiologically feasible. It is also of considerable interest that LPA activates the MAP kinase cascade (see also [12]), raising the possibility that a kinase associated with this cascade is responsible for Cx43 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…This variation in protocol might account for Supplemental Material can be found at: ( 74 ). Following CNS injury, ischemia, or events that damage the blood brain barrier, LPA-like activity increased within the cerebrospinal fl uid , levels of LPA within the CNS increased up to 10 µM (75)(76)(77)(78), and levels of ATX increased within astrocytes neighboring a lesion of the adult rat brain ( 79 ). Our data using human cells suggest that the presence of LPA in regions of neurogenesis within the CNS may modify NS/PC survival and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Because activated platelets copiously secrete the mediator, it has been suggested that aggregated platelets are the primary source of the serum LPA (14,18). This source, coupled with the mitogenic and chemotactic properties of LPA, has prompted the hypothesis that the phospholipid is an important mediator of wound healing (12). Additionally, several of the known effects of LPA are consistent with a potential proinflammatory or proimmune function.…”
mentioning
confidence: 96%
“…During membrane phospholipid biosynthesis, LPA is formed by acylation of sn-glycerol-3-phosphate or by acylation of dihydroxyacetone phosphate followed by reduction of the acyl-dihydroxyacetone phosphate (10). In contrast, LPA that is rapidly generated in the plasma membrane of thrombin-activated platelets and growth factorstimulated fibroblasts (11,12) appears to arise from hydrolysis of phosphatidic acid (PA) by a phospholipase A 2 (13)(14)(15). Additionally, Fourcade et al (16) have demonstrated that a secretory phospholipase A 2 acts upon membrane microvesicles shed from activated cells to convert PA to LPA.…”
mentioning
confidence: 99%